Pengaruh Pendekatan Pembelajaran Deep Learning terhadap Motivasi Belajar Matematika pada Siswa Kelas IV di SDK Santo Yoseph 4 Kupang - Maria Flaviana Seran; Mbuik, Heryon Bernard; Koli, Radka Bodkova (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary schools is frequently characterized by low student motivation due to teacher-centered instructional practices and limited opportunities for meaningful engagement. This study aimed to examine the effect of the Deep Learning instructional approach on fourth-grade students' motivation to learn mathematics at SDK Santo Yoseph 4 Kupang. A quantitative approach employing a quasi-experimental method with a One-Group Pretest–Posttest Design was adopted. The participants consisted of 29 fourth-grade students selected through total sampling. Data were collected using a 20-item mathematics learning motivation questionnaire based on six indicators of learning motivation and analyzed using descriptive and inferential statistics with IBM SPSS Statistics version 22. The descriptive findings revealed that the mean motivation score increased from 56.66 on the pretest to 71.55 on the posttest, indicating an improvement from the